Internet representations of voluntourism fail to effectively integrate tourism and volunteering. Issue 1 (1st January 2020) - Inversini, Alessandro; Rega, Isabella; van Zyl, Izak
Abstract: Voluntourism as a form of philanthropic tourism has become an increasingly popular research topic but there is a paucity of literature on the complex interplay between voluntourism and the internet. Specifically, there is sparse evidence on how the internet mediates ideas and representations of voluntourism. Building on prior research in the information search field, we examine the online representation of voluntourism in South Africa – a popular destination for voluntourists. Querying a popular search engine using a combination of keywords, we retrieved 600 web pages, which were stored and analysed using a predefined codebook. We employ social representation theory as an analytical tool for interpreting the retrieved search engine content. Results indicate three distinct clusters: the first is related to the volunteering experience itself, the second focuses on the touristic experience, and the third encompasses the voluntourism journey as a whole. These clusters reveal a misleading representation of voluntourism in the online space: voluntourism is predominantly represented as a cultural experience, with a strong presence of its key components (i.e. tourism and volunteering) and only a weak holistic view that integrates the two. In light of these findings, we conclude that internet representations of voluntourism do not integrate tourism and volunteering impact fully, which counteracts effective marketing of the industry. These results help voluntourist organisations in South Africa and internationally to improve their online targeting mechanisms to promote their services more accurately.